2021
DOI: 10.1029/2021ja029667
|View full text |Cite
|
Sign up to set email alerts
|

A New MEPED‐Based Precipitating Electron Data Set

Abstract: Space weather has important consequences for Earth's middle and upper atmosphere. Solar flares launched from the Sun release copious numbers of high energy photons that cause large ionization increases in the D and E regions of the ionosphere (Donnelly, 1976;Pettit et al., 2018;Tsurutani et al., 2009;Woods et al., 2004). Many strong solar flares are accompanied by coronal mass ejections (CMEs), which are large magnetic storms that eject massive numbers of solar energetic particles (mostly protons) into the hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…In the mesosphere, NO x is primarily comprised of NO. On the other hand, Pettit et al (2021) showed that including medium energy electron (MEE) sources of ionization in WACCM resulted in better agreement between simulated and observed NO concentrations in the polar winter mesosphere, though midlatitude NO was still underestimated in the model. A study that imposes both improved dynamics and MEE sources is long overdue.…”
Section: The Energetic Particle Precipitation "Indirect Effect"mentioning
confidence: 98%
See 1 more Smart Citation
“…In the mesosphere, NO x is primarily comprised of NO. On the other hand, Pettit et al (2021) showed that including medium energy electron (MEE) sources of ionization in WACCM resulted in better agreement between simulated and observed NO concentrations in the polar winter mesosphere, though midlatitude NO was still underestimated in the model. A study that imposes both improved dynamics and MEE sources is long overdue.…”
Section: The Energetic Particle Precipitation "Indirect Effect"mentioning
confidence: 98%
“…As depicted in Figure 1, the MPV acts to couple the atmosphere via the transport of nitrogen oxides (NO x ) produced by energetic particle precipitation (EPP) from the mesosphere and lower thermosphere (MLT) down to the stratosphere where the NO x can destroy ozone. Understanding why models underestimate this EPP "indirect effect" was identified as a priority in the last decadal survey but has yet to be fully realized (Randall et al, 2015;Pettit et al, 2019Pettit et al, , 2021. Underestimates in simulated NO x are likely due to a combination of erroneous transport (Siskind et al, 2015) and electron source specifications.…”
Section: The Energetic Particle Precipitation "Indirect Effect"mentioning
confidence: 99%
“…It should be noted that POES has limited spatial coverage between 10 and 15 MLT (see Figure S1 in Supporting Information S1) in years after the MEPED instrument aboard NOAA16 was no longer in operation (2005). The POES Space Environment Monitor (SEM/2) MEPED data used in this study uses processing as described by Pettit et al (2021) and is referred to as the MEPED Precipitating Electron (MPE) data set. The MPE data set calculates differential flux using all three POES electron channels as well as the P6 channel, which can be used as a proxy for relativistic electrons (Yando et al, 2011).…”
Section: Particle Flux Measurementsmentioning
confidence: 99%
“…The POES Space Environment Monitor (SEM/2) MEPED data used in this study uses processing as described by Pettit et al. (2021) and is referred to as the MEPED Precipitating Electron (MPE) data set. The MPE data set calculates differential flux using all three POES electron channels as well as the P6 channel, which can be used as a proxy for relativistic electrons (Yando et al., 2011).…”
Section: Instrumentation and Datasetsmentioning
confidence: 99%
“…The construction of the MEPED instrument minimized the cross-contamination between the proton and electron channels. However, low energy protons at the right incidence angle are able to enter the electron detector where they produce a false count (Pettit et al, 2021). To account for proton contamination, we use the MEPED dataset from Pettit et al (2019Pettit et al ( , 2021 which corrects for proton contamination by fitting the proton detector counts to obtain differential fluxes that are subtracted from the electron channels.…”
Section: Medium Energy Proton and Electron Detector (Meped) Observationsmentioning
confidence: 99%